Hyperreality and global culture - Perry, Nick, 1942- (Routledge social futures series., 1998)
First full length discussion of hyperreality. Perry provides the reader with a full length discussion of the origins of the concept, nuances of meaning and case studies of hyperrealism - European tourism, American television etc.